Do Natural Hazards Cause International Migration? - Jasmin Gröschl; Thomas Steinwachs (Center for Economic Studies and ifo Institute (CESifo), 2016)
The estimated amount of people affected by natural hazards stands at a staggering number of about 243 million people per year. While not all of the affected move across borders, international migration potentially provides an adaptation mechanism to natural hazards. The aim of this paper is to assess whether natural hazards induce international migration from a macro perspective. We construct a stylized theoretical gravity model of migration that includes hazards as random shocks. To estimate this model, we deploy exogenous data on geological and meteorological hazards from 1980 to 2010. We combine this data with the World Bank's Global Bilateral Migration Database. Overall, our results suggest little evidence that natural hazards affect medium to long-run international migration. However, considering heterogeneity across income groups, we find that particularly middle-income countries experience significant push and pull effects on migration from natural hazards.
Keywords: F22; O15; Q54; 330; natural hazards; international migration; gravity model; heterogeneity across income groups